Are There International R and D Spillovers Among Randomly Matched Trade Partners? : A Response to Keller - Coe, David (IMF Working Papers; Working Paper ;, 1999)
Keller (1998) reexamines Coe and Helpman's (1995) analysis of international R and D spillovers focusing on the weights used to define the foreign R and D capital stock. Keller creates 'random' weights and shows that they give rise to positive estimates of international R and D spillovers, casting doubts on the robustness of Coe and Helpman's findings. We show that Keller's 'random' weights are essentially simple averages with a random error. We derive alternative random weights and present regressions showing that when they are used to define the foreign R and D capital stock, the estimated international R and D spillover estimates are nonexistent, as would be expected.